Advanced Financial Accounting For Business Admin- AF187- 202202 - Arias Picón, Norma Beatriz (2022)
Course Overview This course expands on your existing knowledge of the financial accounting and reporting process from a user¿s perspective. We will move beyond the knowledge gained in the introductory financial accounting course taken as a prerequisite. You will learn how the economic transactions of an enterprise are reported in the financial statements and related disclosures. The goal of the course is to provide you with a basic set of skills that can be used to understand and analyze financial statements. Prerequisite Requirements You will need to have successfully completed ACCT200 Introductory Financial Accounting and ACCT210 Introductory Managerial Accounting prior to taking this course.